Cationic liposomes induce cell necrosis through lysosomal dysfunction and late-stage autophagic flux inhibition. (December 2016) - Yang, Kaixuan; Lu, Ying; Xie, Fangyuan; Zou, Hao; Fan, Xiaoyu; Li, Bohua; Li, Wei; Zhang, Wei; Mei, Lin; Feng, Si-shen; Yin, You; Liu, Yan; et al.
Aim: The application of cationic liposomes (CLs) as nonviral vectors is hampered by their cellular toxicity. Thus we aim to investigate the mechanisms underlying the cellular toxicity of CLs.Materials & methods: The effect of CLs on the autophagic flux, autophagosome-lysosome fusion, lysosome membrane permeabilization and cell necrosis of liver cells was investigated.Results & conclusion: Our results reveal a novel mechanism of CL-induced cell necrosis involving the induction of lysosome membrane permeabilization and late-stage autophagic flux inhibition that resulted in cytoplasmic release of cathepsin B, mitochondrial dysfunction and reactive oxygen species production, which are the key mediators of cell necrosis. Our study is important for revealing the cellular toxicity of CLs and designing safer gene delivery systems.